The Association of Rural Elementary School Environmental Characteristics with Children's Physical Activity Levels at School - Katherine Gunter; Jennifer A Jackson; Patrick Abi Nader; Deborah H John (Shiraz University of Medical Sciences, 2018)
Background: The importance of school settings for obesity prevention efforts may be most critical in low-income rural areas where healthy eating and physical activity (PA) resources are scarce. This study examined the association of rural elementary school environmental characteristics with children's PA behaviors at school. Methods: Analyses were based on objectively measured height, weight, and PA data from 1443 first to sixth graders attending six rural elementary schools in Oregon. The School Physical Activity and Nutrition Environment Tool (SPAN-ET) was used to measure elementary school PA policy, practice, and physical environments. Multivariable linear regressions were used to examine associations of 29 SPAN-ET PA measurement criteria, with total PA (light, moderate, vigorous; min/d), and moderate-to-vigorous PA (MVPA; min/d), adjusting for child sex, age, and BMI z-score. Results: Our final sample included 755 boys and 688 girls (9 ± 1.7 years); Of them, 16% were overweight and 21% obese. Total PA was positively associated with 21 SPAN-ET PA criteria (unadjusted P value ranged from 0.7 to 0.001; adjusted P < 0.0125); 15 criteria were positively associated with MVPA (unadjusted P value ranged from 0.313 to 0.001; adjusted P < 0.00625). Conclusions: Characteristics of rural school environments are associated with children's PA behaviors at school. Structured physical education, classroom-based PA, PA messaging, and adequate indoor/outdoor space are important correlates of PA in rural schools.